THE STUDENTS' RESPONSES: IMPLEMENTATION OF AN ELECTRONIC MODULE ON THE CLASSIFICATION OF LIVING THINGS INTEGRATED WITH SIDOARJO LOCAL WISDOM - Sartika, Septi Budi; Wulandari, Ria; Efendi, Nur (Program Studi Pendidikan IPA FKIP Universitas Jember, 2024)
Positive learning response is an important element of learning activities. Learning response to learning can attract students' attention in learning activities carried out. The purpose of this study was to analyze student responses after using an electronic module on the classification of living things integrated with Sidoarjo local wisdom. This research method is a quantitative research method using instruments in the form of questionnaires given to students. Based on the research that has been done, it shows that student responses when using the electronic module of living creature classification material integrated with Sidoarjo local wisdom obtained a good response with a percentage of 45.85%. Further research is expected to improve and develop 4 aspects of electronic modules based on local wisdom of other science materials, namely presentation of material, language, usefulness and graphics in order to get student response criteria at least in the good category.